THE ABUNDANCE OF POISONOUS BENTHIC DINOFLAGELLATE IN SEAWEED Sargassum sp IN MALANG RAPAT WATERS BINTAN REGENCY RIAU ISLANDS PROVINCE - Dilla Andini; Irvina Nurrachmi; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Dinoflagellates are phytoplankton which, besides being planktonic, are also benthic which live in association with seagrasses, macroalgae, coral fractures and sand. Dinoflagellates acts as a primary producer in waters. This research was carried out in Mei 2018 in the waters of Malang Rapat Village, Bintan Regency, Riau Islands Province. This study aims to determine the concentration of nitrates and phosphates in the waters, to find out the abundance of toxic benthic dinoflagellates on Sargassum sp seaweed and to see the relationship of nitrate and phosphate concentrations with the abundance of toxic benthic dinoflagellates. The research method used is a survey method in which the sampling location is determined by purposive sampling. Measurements of water quality were carried out directly in place and further research in laboratory which consisting of physical and chemical parameters of the waters. In the study found 3 genus of toxic dinoflagelates, namely Prorocentrum, Gambierdiscus and Ostreopsis. The highest dinoflagellate abundance at station 3 was 302,279 cells/g and the lowest at station 4 was 133,529 cells/g. The results of simple linear regression analysis between nitrate concentration has a positive relationship to dinoflagellate abundance with the regression equation y = 187.4 + 317.8 x and the results of simple linear regression analysis between phosphate concentration have a negative relationship to the abundance of dinoflagellates with the regression equation y = 207 , 5 -206,3 x. Key Word : Dinoflagellate, Sargassum sp, Abundance, Malang Rapat